2019
DOI: 10.2147/cmar.s181740
|View full text |Cite
|
Sign up to set email alerts
|

<p>Pathological risk factors for lymph node metastasis in patients with submucosal invasive colorectal carcinoma</p>

Abstract: BackgroundRisk grade assessment determines therapy in patients with submucosal invasive colorectal carcinoma (CRC). However, treatment decisions are often difficult due to a lack of consensus on which risk factors should be considered. We aimed to identify predictive risk factors for lymph node metastasis (LNM) in a large cohort of submucosal invasive CRC patients from China.Patients and methodsFollowing collection of clinicopathological data and disease-free survival (DFS) rates from 290 patients who underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Although the evidence is too insufficient to draw a conclusion, recent studies have suggested that T1 CRC with invasion deeper than 1000 mm may be considered low-risk as long as other risk factors are absent. [37][38][39] We expect to obtain additional evidence regarding this matter in the future, which will enable treatment decisions to be made with greater precision. This is a systematic review for the long-term prognosis of T1 CRC between ER and surgery, and the strengths of our study arise from the comprehensive inclusion and review of currently available studies and meticulous analyses for major outcomes and among different subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Although the evidence is too insufficient to draw a conclusion, recent studies have suggested that T1 CRC with invasion deeper than 1000 mm may be considered low-risk as long as other risk factors are absent. [37][38][39] We expect to obtain additional evidence regarding this matter in the future, which will enable treatment decisions to be made with greater precision. This is a systematic review for the long-term prognosis of T1 CRC between ER and surgery, and the strengths of our study arise from the comprehensive inclusion and review of currently available studies and meticulous analyses for major outcomes and among different subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…The main non-invasive diagnostic method is enhanced CT and PDG-PET, however, they both involve radiation exposure that some patients are unwilling to accept (15). In recent years, with the development of molecular biology, the application of serum tumor markers in the auxiliary diagnosis of lung cancer and the monitoring of recurrence and metastasis has achieved good results (16,17). NSE is recognized as a highly sensitive tumor marker in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…11 A recent study with 290 patients with endoscopically resected malignant polyps who underwent surgical resection also reported tumor budding as one of the risk factors for LNM, found in 42% of tumors with LNM compared with 18% in LNM-negative tumors (OR, 2.3; 95% CI, 1.1-5.0). 76 Recently, recommendations of an international Tumor Budding Consensus Conference were published in a consensus agreement defining tumor budding and specifically separated tumor budding from tumor grading. 77 The international group achieved consensus on important statements, including that tumor budding is defined as a single tumor cell or a cell cluster consisting of 4 or fewer tumor cells; tumor budding is an independent predictor of LNM in malignant polyps and should be assessed in addition to other clinicopathologic features in a multidisciplinary setting and be part of the CRC reporting system.…”
Section: Tumor Buddingmentioning
confidence: 99%